SOSIALISASI DAN LAYANAN PEMELIHARAAN SEPEDA MOTOR GRATIS DI DESA KALISARI KECAMATAN TEMPURAN KABUPATEN MAGELANG - Aryananta Lufti; Harjanto, Budi; Sukahar (JURNAL NAGARA BHAKTI, 2025)
The majority of kalisari villagers, apart from being students, also work as private employees and farmers. To support mobilization in everyday life, people usually use two-wheeled vehicles in the form of motorcycles. Abnormal vehicle conditions are one of the factors causing accidents. By doing regular maintenance, it is expected that the performance of the vehicle can be maintained properly. Akmil Defense mechanical engineering study program, with concrete steps to contribute to the Kalisari village community through socialization and free motorcycle service.Free motorcycle service activities in the framework of Community Service Department of Defense Mechanical Engineering Akmil successfully met the target where there are 70 motorcycles that get free service. The implementation of motorcycle service was carried out for two days, where the first day successfully served 35 motorcycles and the second day served 35 motorcycles. In the implementation of vehicle service, there are no special complaints from the public regarding the vehicle, so that the service carried out is periodic service such as Carburetor service, Valve stel, Oil Change, addition of motorcycle tires, as well as checking and adjusting other components.